GASTRONOMY IN THE MEJOTAN TRADITION AS A TOURIST ATTRACTION IN ABIANSEMAL DISTRICT, BADUNG REGENCY - Tri Sutaguna, I Nyoman; Muriawan Putra, Agus (Yayasan Pendidikan Belajar Berdikari, 2025)
Understanding the advantages and characteristics of gastronomic tourism, as mentioned, will greatly assist planners in developing it. Synergy with agriculture and livestock can be fostered in coastal areas with beautiful beaches, creating synergy between upstream and downstream sectors. Developing agricultural and livestock products in upstream areas, packaged into engaging activities, can also become a tourist attraction. One culinary product development well-known among Balinese people is preserving the mejotan culture as an authentic Balinese gastronomy. In contrast, tourism practitioners reported that they were aware of the mejotan tradition, but lacked any idea of ​​how to package and sell it in villas or restaurants in the Abiansemal District of Badung. This is truly a missed opportunity, without providing the intended benefits.The food ingredients used as offerings in the mejotan tradition are sourced locally, such as rice, cassava, and pork, along with other equipment needed to process these ingredients. These ingredients, derived from local agriculture and livestock, undergo a traditional processing process, and are then used in the mejotan tradition. The purpose of this research is to develop the gastronomic potential of the mejotan tradition as a tourist attraction in the Abiansemal District of Badung, Bali.The approach used in this study is qualitative. In qualitative research, the phenomena used to determine the variables to be studied are holistic, so the research will not be determined based solely on the research variables, but rather on the entire social situation, encompassing the place, actors, and activities that interact synergistically.